2020
DOI: 10.5194/bg-17-2315-2020
|View full text |Cite
|
Sign up to set email alerts
|

Ocean deoxygenation and copepods: coping with oxygen minimum zone variability

Abstract: Abstract. Increasing deoxygenation (loss of oxygen) of the ocean, including expansion of oxygen minimum zones (OMZs), is a potentially important consequence of global warming. We examined present-day variability of vertical distributions of 23 calanoid copepod species in the Eastern Tropical North Pacific (ETNP) living in locations with different water column oxygen profiles and OMZ intensity (lowest oxygen concentration and its vertical extent in a profile). Copepods and hydrographic data were collected in ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 79 publications
1
30
0
Order By: Relevance
“…3-5). The low density of foraminifera in the oxycline is an interesting contrast to the vertical distributions of many metazoan species that often peak in abundance in the upper oxycline and decline in the core of the OMZ (Maas et al, 2014;Wishner et al, 1995Wishner et al, , 2013Wishner et al, , 2020b. Based on the mixed assemblage and low densities, we hypothesize that planktic foraminifera are largely absent from the upper oxycline, with populations restricted to either the oxygenated photic zone habitat above or the OMZ below.…”
Section: Distinct Omz Community Of Planktic Foraminiferamentioning
confidence: 86%
See 2 more Smart Citations
“…3-5). The low density of foraminifera in the oxycline is an interesting contrast to the vertical distributions of many metazoan species that often peak in abundance in the upper oxycline and decline in the core of the OMZ (Maas et al, 2014;Wishner et al, 1995Wishner et al, , 2013Wishner et al, , 2020b. Based on the mixed assemblage and low densities, we hypothesize that planktic foraminifera are largely absent from the upper oxycline, with populations restricted to either the oxygenated photic zone habitat above or the OMZ below.…”
Section: Distinct Omz Community Of Planktic Foraminiferamentioning
confidence: 86%
“…Plankton tows sampled depths between 0 and 1000 m, across dissolved oxygen levels between 0.03 and 4.93 mL L −1 and temperatures ranging from 4.5 to 22.9 • C. Although smallscale oxygen features and their depth relative to the oxycline and OMZ varied somewhat (Wishner et al, 2018(Wishner et al, , 2020b, the overall structure of the water column was consistent across tows. A warm, oxygenated surface mixed layer overlaid an oxygen-depleted OMZ, with gradual cooling at increasing depth below the thermocline.…”
Section: Hydrological Data From Towsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the seafloor, oxygen patterns resemble those for pH, with highest dissolved oxygen concentrations in the North Atlantic, and lowest concentrations in the North Pacific (Sweetman et al, 2017). Oxygen strongly influences benthic fauna density, biodiversity, species distributions, taxonomic composition, food web structure, biogeochemical cycling, body size and specieslevel population and physiological rates (Levin and Gooday, 2003;Muthumbi et al, 2004;Laffoley and Baxter, 2019;Wishner et al, 2020). In the deep sea, the strongest influence of oxygen occurs at bathyal depths (200-1200 m) within oxygen minimum zones, but particularly in the prevalent extreme OMZs in the North and Eastern Pacific Ocean, Northern Indian Ocean, and off west Africa (Helly and Levin, 2004) as well as the Western Indian Ocean (Muthumbi et al, 2004).…”
Section: Stratification By Latitude As a Proxy For Climate Related Vamentioning
confidence: 99%
“…The lack of community-level response to diurnal and weekly oxygen variability seen in our data may not be surprising given that animals have several ways that they can respond to stressful conditions, which would not affect community-level abundance, diversity, or composition patterns. For example, fish can become less active and reduce metabolic demands (Richards, 2009(Richards, , 2010, or they can decrease feeding behavior (Wu, 2002;Nilsson, 2010) during periodic hypoxia. We observed that animals were less active in the deeper deployments, but it is unclear if this is due to the lower-oxygen conditions or other environmental covariates.…”
Section: Observations Of Community Responses To High-frequency Enviromentioning
confidence: 99%